EXPLORING PEDAGOGIES OF AFFECT IN SECONDARY SCHOOL PHYSICAL EDUCATION FOR ENHANCED EMOTIONAL WELL-BEING - Rita Komalasari (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper aims to comprehensively analyze the pedagogies of affect in secondary school physical education, with a specific focus on their role in promoting students' emotional well-being. It addresses existing gaps in the literature by integrating Self-Determination Theory (SDT), examining teacher awareness and motivation, promoting a holistic concept of health, considering the Indonesia educational context, and utilizing a pragmatic mixed methods approach. A literature study approach is employed. The findings reveal that teacher engagement in pedagogies of affect significantly influences students' emotional well-being. Need-supportive teaching behaviors directly impact affective learning outcomes, emphasizing the importance of autonomy, relatedness, and intrinsic motivation. Teachers' self-awareness and the quality of teacher-student relationships play pivotal roles in shaping emotional experiences in physical education. This research contributes novel insights into the field, offering a comprehensive framework for promoting emotional well-being in physical education. It highlights the transformative potential of education in nurturing not only the bodies but also the hearts and minds of young individuals in the pursuit of overall well-being.